1983
DOI: 10.1007/bf02405103
|View full text |Cite
|
Sign up to set email alerts
|

Hormonal alterations in experimental diabetes: Role of a primary disturbance in calcium homeostasis

Abstract: Summary. Chronic diabetes mellitus in the rat isattended by a reduced bone turnover and growth arrest, decreased circulating immunoreactive parathyroid hormone (iPTH), and hypercorticosteronism. Since chronic insulin deficiency in the rat is associated with intestinal hyperabsorption of calcium and a positive calcium balance that may account for the decreased iPTH, as well as other hormonal alterations observed in these animals, we studied the effect of long-term (5 week) dietary calcium restriction (0.1% Ca, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

1983
1983
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 26 publications
1
5
0
Order By: Relevance
“…However, other reports have failed to confirm these results and suggested that PTH acts predominantly on the Krebs cycle [35]. Circulating parathyroid hormone is decreased in chronically insulin-deficient rats [6] and significantly increased by dietary calcium restriction, without any appreciable change in immunoreactive insulin [25]. Since cartilage tissue from diabetic animals reared on a low calcium diet demonstrated a significant increase in lactate production with a normalization of glycolysis, it is possible that the defect in glycolytic activity of diabetic rat cartilage may be related to a state of relative hypoparathyroidism.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…However, other reports have failed to confirm these results and suggested that PTH acts predominantly on the Krebs cycle [35]. Circulating parathyroid hormone is decreased in chronically insulin-deficient rats [6] and significantly increased by dietary calcium restriction, without any appreciable change in immunoreactive insulin [25]. Since cartilage tissue from diabetic animals reared on a low calcium diet demonstrated a significant increase in lactate production with a normalization of glycolysis, it is possible that the defect in glycolytic activity of diabetic rat cartilage may be related to a state of relative hypoparathyroidism.…”
Section: Discussionmentioning
confidence: 95%
“…Chronically insulinopenic rats maintained elevated plasma calcium levels despite severe hypercalciuria and a pronounced decrease in bone turnover [6]. Diabetic animals reared on a low calcium diet responded with an appropriate increase in plasma iPTH and urinary phosphate excretion [25]. Furthermore, hypercorticosteronism was corrected by calcium restriction in diabetic animals.…”
Section: Discussionmentioning
confidence: 99%
“…Probably, an absolute lack of insulin reduces calcium incorporation into the cells and increase concentration of this element in serum [34]. High concentrations of glucagone, probably through the inhibition of alimentary duct motorics, can increase intestinal absorption of calcium and magnesium [35]. Increased levels of calcium through increased levels of calcitonin [34] stimulate estrogen production by increasing the activity of cytochrome P450 aromatase and P450arom gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…Employing short-term (2-week) animal models of streptozotocin diabetes, the low BMD observed in insulinopenic diabetes was earlier explained by secondary hyperparathyroidism and increased bone resorption resulting from a negative calcium balance (impaired intestinal calcium absorption; hypercalciuria) (69,70). Using more appropriate animal models of chronic diabetes (8-10 weeks), and employing time-spaced tetracycline labelled bone histomorphometry, bone formation and resorption were found to be markedly suppressed (71,72,73,74).…”
Section: Bone Turnovermentioning
confidence: 99%